Presence of KREMEN receptors for DKK1 in the preimplantation bovine embryo - Thiago Fernandes Amaral; Yao Xiao; Surawich Jeensuk; Tatiane Silva Maia; Camila J Cuellar; Chloe A Gingerich; Tracy L Scheffler; Peter J Hansen (Bioscientifica, 2023)
The WNT inhibitory protein DKK1 has been shown to regulate the development of the preimplantation embryo to the blastocyst stage. In cattle, DKK1 increases the number of trophectoderm cells that are the precursor of the placenta. DKK1 can affect cells by blocking WNT signaling through its receptors KREMEN1 and KREMEN2. Here it was shown that the mRNA for KREMEN1 and KREMEN2 decline as the embryo advances in development. Nonetheless, immunoreactive KREMEN1 was identified in blastocysts using western blotting. DKK1 also decreased the amount of immunoreactive β-catenin in blastocysts, as would be expected if DKK1 was signaling through a KREMEN-mediated pathway. Thus, it is likely that KREMEN1 functions as a receptor for DKK1 in the preimplantation bovine embryo.